The Role of Contrast-Enhanced Imaging Methods in Breast Cancer Early Diagnostics and Treatment Planning - I. Е. Tyurin; N. I. Rozhkova; E. V. Artamonova; E. A. Busko; V. V. Didenko; A. D. Zikiryakhodzhaev; M. S. Karpova; G. Е. Kvetenadze; P. V. Krivorot’ko; M. L. Mazo; A V. Petrovsky; О. S. Puchkova; et al. (Вестник рентгенологии и радиологии)
Оn March 27, 2023, а multidisciplinary Advisory Board meeting was held in Moscow with the participation of Е.V. Artamonova, Е.А. Busko, V.V. Didenko, А.D. Zikiryakhodzhaev, М.S. Karpova, G.Е. Kvetenadze, P.V. Krivorot’ko, М.L. Mazo, А.V. Petrovsky, О.S. Puchkova, S.V. Serebryakova under the chairmanship of I.Е. Tyurin and N.I. Rozhkova. The participants discussed different issues of early diagnostics and treatment planning of breast cancer. We present the conclusion made by the Advisory Board.